Travelling motivation for Malaysian to nature and cultural destinations - Cheng, Fan Fah; Cheng, Seow Voon (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
There are various factors that motivate people to travel. Just like other products, tourists generally undergo several stages in their decision making before finally deciding on the destination to visit. Although there are numerous studies done on travel motivation so far, the latest travel motivations among Malaysians are somewhat unknown. This study, therefore, was carried out to identify the latest demographic variables of Malaysians on their travel motives. It is important to understand if travel motivations among Malaysians are affected by their demographic variables that include factors such as gender, age group and income level. A 17-item questionnaire was used to survey 200 respondents on their travelling motivation, while that the respondents are basically motivated to visit certain nature and cultural destination. Another 18 items were utilised to measure the attractions. Findings of this study showed destinations because of the attractions at the places. Furthermore, the survey results also showed that the travel motivations of Malaysians are directly influenced by their gender, age, income level and education level.